Spectrophotometric Kinetic Methods for the Determination of Paracetamol in Pure Form and Pharmaceutical Preparations - Q. Al-Abachi, Mouyed; A. Al-Safi, Sarria; S. Al-Ward, Hind (Iraqi Journal of Science, 2023)
Simple and sensitive kinetic methods are developed for the determination of Paracetamol in pure form and in pharmaceutical preparations. The methods are based on direct reaction (oxidative-coupling reaction) of Paracetamol with o-cresol in the presence of sodium periodate in alkaline medium, to form an intense blue-water-soluble dye that is stable at room temperature, and was followed spectrophotometriclly at λmax= 612 nm. The reaction was studied kinetically by Initial rate and fixed time (at 25 minutes) methods, and the optimization of conditions were fixed. The calibration graphs for drug determination were linear in the concentration ranges (1-7 μg.ml-1) for the initial rate and (1-10 μg.ml-1) for the fixed time methods at 25 min. The methods were applied successfully for the determination of Paracetamol in pharmaceutical.